Evidence for transforming Growth Factor-Beta 3 gene polymorphism in non-syndromic cleft lip and palate patients from Indian sub-continent - Shaikh, S.; Ravenndranath, R.; Banerjee, M.; Joseph, A.; Jahgirdar, P. (Medicina oral, patología oral y cirugía bucal, 2012)
Orofacial clefts are major human birth defects with complex etiology. Previous studies have proposed Transforming growth factor - beta 3 (TGF-β3) gene as a key player in contributing to non-syndromic cleft lip and palate, however none of the studies have yet included Indian population. Hence this study was designed to detect TGF-β3 gene polymorphism in nonsyndromic cleft lip and palate patients from Indian population which is genetically distinct from previously studied populations. Peripheral blood samples of forty non-syndromic cleft lip and palate patients and forty unaffected individuals were collected for a case - control study design. Ethical clearance from the institutional review board and informed consent from all subjects was obtained. DNA extracted from the cases and controls was amplified using polymerase chain reaction (PCR) with TGF-β3 specific primers. The obtained fragments were sequenced and TGF-β3 gene polymorphisms were assessed based on the number of CA repeats. Chi -square test was used to compare the case and control groups. Results showed a significant difference in the number of CA repeats between the case and the control groups (p=0.01). This study confirms the crucial role of TGF-β3 in the fusion of palatal shelves during development and further, provides novel evidence of TGF-β3 gene polymorphism in the etiology of nonsyndromic cleft lip and palate in Indian subpopulation.